2021
DOI: 10.1186/s40478-021-01149-y
|View full text |Cite
|
Sign up to set email alerts
|

Early alterations of neurovascular unit in the retina in mouse models of tauopathy

Abstract: The retina, as the only visually accessible tissue in the central nervous system, has attracted significant attention for evaluating it as a biomarker for neurodegenerative diseases. Yet, most of studies focus on characterizing the loss of retinal ganglion cells (RGCs) and degeneration of their axons. There is no integrated analysis addressing temporal alterations of different retinal cells in the neurovascular unit (NVU) in particular retinal vessels. Here we assessed NVU changes in two mouse models of tauopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Previous studies demonstrated that α-syn triggers neuroinflammation, and that, in turn, inflammation increases α-syn phosphorylation and pathology in synucleinopathies ( Lee et al, 2010 ; Tansey and Goldberg, 2010 ; Ramirez et al, 2017 ; Ferreira and Romero-Ramos, 2018 ). Furthermore, retinal inflammation has been linked to both swelling of the outer retina and ERG deviations, and may therefore underlie -at least in part- the OCT and ERG abnormalities that we observed in the Thy1-h[A30P]α-syn mice ( Mirza and Jampol, 2013 ; Petzold, 2016 ; Pisa et al, 2021 ; Xia et al, 2021 ). Hence, we next investigated macroglia and microglia reactivity and water homeostasis in the retina.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies demonstrated that α-syn triggers neuroinflammation, and that, in turn, inflammation increases α-syn phosphorylation and pathology in synucleinopathies ( Lee et al, 2010 ; Tansey and Goldberg, 2010 ; Ramirez et al, 2017 ; Ferreira and Romero-Ramos, 2018 ). Furthermore, retinal inflammation has been linked to both swelling of the outer retina and ERG deviations, and may therefore underlie -at least in part- the OCT and ERG abnormalities that we observed in the Thy1-h[A30P]α-syn mice ( Mirza and Jampol, 2013 ; Petzold, 2016 ; Pisa et al, 2021 ; Xia et al, 2021 ). Hence, we next investigated macroglia and microglia reactivity and water homeostasis in the retina.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, from the viewpoint of researchers engaged in eye-related basic science, the lack of microglia-isolating protocol specialized for retina may appear to be the most notable inadequacy in this field, since retina is the unique observable tissue in the central nervous system, and this advantage makes adult rat modeling of retinal diseases an excellent reference for the study of the central nervous system in terms of both structure and function. Therefore, our research is devoted to remedy this inadequacy and try to develop a practical methodology as a research tool to facilitate associated scientific work, which focuses on potential mechanisms that microglia may be involved in the posterior segment of the eye, especially in the condition of glaucoma [ 34 , 35 ]. The density of isolated microglia obtained in different tissues is various.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on P301S mice aiming to distinguish more clearly between the impact of tau and amyloid have revealed the occurrence of an RGC axonopathy associated with reactive microgliosis and vasculopathy [ 18 , 65 ]. Xia et al [ 65 ] recently showed that p-tau was distributed throughout the retina in a mouse models of tauopathy in line with previously reported presence of p-tau in both retina and optic nerve soluble protein extracts coming from 5-months-old P301S mice [ 38 ]. Heavily burdened p-tau was also identified in the visual cortex of rTg4510 mouse model of tauopathy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%